2020
DOI: 10.3390/polym12081851
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Electrochemical Properties of Porous Carbon Nanofiber Electrodes Derived from New Precursor Polymer: 6FDA-TFMB

Abstract: Porous carbon nanofibers (CNFs) with high energy storage performance were fabricated with a single precursor polymer, 6FDA-TFMB, without the use of any pore-generating materials. 6FDA-TFMB was synthesized, electrospun, and thermally treated to produce binder-free CNF electrodes for electrochemical double-layer capacitors (EDLCs). Highly porous CNFs with a surface area of 2213 m2 g−1 were prepared by steam-activation. CNFs derived from 6FDA-TFMB showed rectangular cyclic voltammograms with a specific capacitanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…6FDA-based PIs are considered to be excellent precursor polymers for highly porous carbon [ 10 , 11 , 40 ]. During thermal treatment, the decomposition of bulky fluorinated substituents in the 6FDA unit can generate pores, resulting in a high surface area and high porosity in the resultant CNFs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…6FDA-based PIs are considered to be excellent precursor polymers for highly porous carbon [ 10 , 11 , 40 ]. During thermal treatment, the decomposition of bulky fluorinated substituents in the 6FDA unit can generate pores, resulting in a high surface area and high porosity in the resultant CNFs.…”
Section: Resultsmentioning
confidence: 99%
“…It was also reported that CNFs derived from crosslinked 6FDA–durene exhibited a high specific capacitance of 301 F/g compared to that of non-treated ones (205 F/g) with KOH [ 43 ]. CNFs derived from 6FDA-2-2′-bis(trifluoromethyl) benzidine (TFMB) were also reported, and steam-activated CNFs showed a specific capacitance of 292 F/g at 10 mV/s with KOH [ 11 ]. It seems that the addition of PVDF has a comparable effect on improving surface porosity and energy storage performance with pre- (surface crosslinking of PI nanofibers before carbonization) or post-treatment (steam activation of carbonized PI nanofibers).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, additional methods, such as small-angle X-ray or neutrons scattering (SAXS, SANS) [ 53 , 54 , 55 , 56 , 57 , 58 ], X-ray diffraction (XRD) [ 59 , 60 , 61 ], high-resolution transmission (HRTEM) and scanning (SEM) electron microscopies [ 59 , 62 ], nuclear magnetic resonance (NMR) spectroscopy with cryoporometry and relaxometry [ 15 , 63 , 64 , 65 ], differential scanning calorimetry (DSC) and thermoporometry [ 66 ], infrared spectroscopy (FTIR), thermogravimetry (TG) and thermoporometry, dielectric relaxation spectroscopy (DRS), thermally stimulated depolarization current (TSDC) and relaxometry, theoretical simulations, etc. [ 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 ] should be used. Besides the textural characteristics, the data of these methods allow one to obtain information on the materials’ behavior under different conditions, which could model real situations related to practical applications.…”
Section: Introductionmentioning
confidence: 99%